STORYTELLING OF DIGITAL TECHNOLOGY AND BRAND IDENTITY AMONG APPLE AND SAMSUNG ADVERTISEMENTS - Muhammad Fil Ardhi Satriandra; Rozi, Romdhi Fatkhur (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study examines how the narratives of digital technology and brand image are constructed in the Apple “Crush! iPad Pro” and Samsung “Creativity Cannot Be Crushed” advertisements, with a focus on the influence of the Social Construction of Technology (SCOT) perspective on branding strategies. Method: A qualitative descriptive approach was employed, analyzing screen captures from both advertisements. The analysis utilized mise en scène elements and was interpreted through Roland Barthes' semiotic theory to uncover the underlying messages. Results: The findings reveal that Samsung projects a brand image that is adaptive and responsive to user needs, whereas Apple constructs a more exclusive brand identity that requires users to align with its technological ecosystem. Novelty: This research contributes to the limited studies integrating SCOT theory with semiotic analysis in the context of brand communication, offering new insights into how different technological perspectives shape brand narratives and visual strategies in competitive advertising.